Reversal of dopamine‐mediated firing inhibition through activation of the dopamine transporter in substantia nigra pars compacta neurons. (23rd July 2018) - Aversa, Daniela; Martini, Alessandro; Guatteo, Ezia; Pisani, Antonio; Mercuri, Nicola Biagio; Berretta, Nicola
Abstract : Background and Purpose: One of the hallmarks of ventral midbrain dopamine‐releasing neurons is membrane hyperpolarization in response to stimulation of somato‐dendritic D2 receptors. At early postnatal age, under sustained dopamine, this inhibitory response is followed by a slow recovery, resulting in dopamine inhibition reversal (DIR). In the present investigation, we aimed to get a better insight into the cellular mechanisms underlying DIR. Experimental Approach: We performed single‐unit extracellular recordings with a multi‐electrode array device and conventional patch‐clamp recordings on midbrain mouse slices. Key Results: While continuous dopamine (100 μM) perfusion gave rise to firing inhibition that recovered in 10 to 15 min, the same effect was not obtained with the D2 receptor agonist quinpirole (100 nM). Moreover, firing inhibition caused by the GABAB receptor agonist baclofen (300 nM) was reversed by dopamine (100 μM), albeit D2 receptors had been blocked by sulpiride (10 μM). Conversely, the block of the dopamine transporter (DAT) with cocaine (30 μM) prevented firing recovery by dopamine under GABAB receptor stimulation. Accordingly, in whole‐cell recordings from single cells, the baclofen‐induced outward current was counteracted by dopamine (100 μM) in the presence of sulpiride (10 μM), and this effect was prevented by the DAT antagonists cocaine (30 μM) and GBR12909 (2 μM). Conclusions and Implications: Our results indicate that the DAT plays a major role in DIR, mediating it under conditions of sustained dopamine exposure, and point to DAT as an important target for pharmacological therapies leading to prolonged enhancement of the dopaminergic signal.